2013
DOI: 10.4322/acr.2013.025
|View full text |Cite
|
Sign up to set email alerts
|

Accessory soleus muscle: a case report and clinical applicability

Abstract: Variations in leg muscle are uncommon. Literature on this subject is scarce, but when those variations are reported they may cause alterations in joint mechanics or cause some discomfort in the leg and foot. The accessory soleus muscle (ASM) is considered an unusual anatomical variation, with an incidence of 0.5-6.0% in the population through studies in cadavers. During routine preparation of study material in the dissection room of the anatomy laboratory of the Escola Superior de Ciências da Santa Casa de Mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Variations in the muscles of the posterior leg region can lead to chronic painful conditions of the ankle. ASM is a condition that manifests itself with the increase in clinical problems caused by advanced age (13)(14)(15)(16)(17). ASM, whose incidence was reported as 0.7%-5.5% in cadaver studies, is usually unilateral and it has been reported to be more (4,18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Variations in the muscles of the posterior leg region can lead to chronic painful conditions of the ankle. ASM is a condition that manifests itself with the increase in clinical problems caused by advanced age (13)(14)(15)(16)(17). ASM, whose incidence was reported as 0.7%-5.5% in cadaver studies, is usually unilateral and it has been reported to be more (4,18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Although congenital, ASM is usually diagnosed in the second or third decade of life when symptoms occur. During this period, muscle mass and physical activity increase, more prominently seen in male patients [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3]11,12 The AS muscle is usually unilateral and shows male predilection, 3,11 presumably due to greater muscle trophism and denser muscle fascia in males. 14 The muscle originates either from the anterior surface of the soleus muscle, the fibula, or the soleal line of the tibia. [1][2][3]11,12 The AS muscle is located superficially to the deep aponeurosis.…”
Section: Accessory Soleus Musclementioning
confidence: 99%
“…1 2 3 11 12 The AS muscle is usually unilateral and shows male predilection, 3 11 presumably due to greater muscle trophism and denser muscle fascia in males. 14…”
Section: Accessory Muscles In the Posteromedial/flexor Compartmentmentioning
confidence: 99%
See 1 more Smart Citation